2010
DOI: 10.1111/j.1365-2672.2010.04843.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted microarray analysis of stationary phase Escherichia coli O157:H7 subjected to disparate nutrient conditions

Abstract: Aims:  To determine how stress response and virulence gene expression of stationary phase (SP) Escherichia coli O157:H7 are affected by nutrient levels. Methods and Results:  A targeted microarray (n = 125 genes) was used to determine the impact of nutrient deprivation [15 min in 3‐(N‐Morpholino)propanesulfonic acid buffer] on SP E. coli O157:H7. In total, 24 genes were significantly affected (>1·5‐fold; P < 0·05) with 17 induced and seven attenuated. Additionally, 11 genes belonging to significantly affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…This is another argument that confirms the validity of our microarray 363 17 results, as already described in similar works (Allen et al 2010;Klitgaard et al 2010; 364 Vasileva et al 2012). 365…”
Section: Discussion 340supporting
confidence: 80%
See 1 more Smart Citation
“…This is another argument that confirms the validity of our microarray 363 17 results, as already described in similar works (Allen et al 2010;Klitgaard et al 2010; 364 Vasileva et al 2012). 365…”
Section: Discussion 340supporting
confidence: 80%
“…The range of log 2 fold changes was apparently low, ranging between 357 1.78 and -2.13, but the numbers obtained were in general quite similar to those observed for 358 transcriptomic analyses of iron starvation in other microorganisms (Allen et al 2010; Basler 359 et al 2006;Brickman et al 2011;Klitgaard et al 2010;Madsen et al 2006). However, very 360 interestingly the changes observed in our work were in most cases for genes grouped in 361 operons, and genes belonging to the same operon underwent, as expected, almost identical 362…”
Section: Discussion 340mentioning
confidence: 53%
“…Therefore, decreased heat tolerance may occur due to the reduced melting point of unsaturated fatty acids within the cell membrane. Other scientist have also indicated that the stress response of bacteria to sublethal environmental stresses such as changes in temperature, starvation, or high osmolarity may provide cross-protection to a variety of postphysical and postchemical stresses including heat and acid (Allen, Lepp, McKellar, & Griffiths, 2010;Arnold & Kaspar, 1995;Erdoğrul, Erbilir, & Toroğlu, 2006;House et al, 2009;Jeong, Baumler, & Kaspar, 2006;Lange & Hengge-Aronis, 1994;Leenanon & Drake, 2001;Nair & Finkel, 2004).…”
Section: Effect Of Ph and Thermal Stress On The Thermal Tolerance Omentioning
confidence: 99%
“…Duffitt et al (8) showed that in water and sterile soil, E. coli 0157 developed a more virulent phenotype, including a higher level of expression of virulence genes. E. coli 0157:H7 also undergoes significant but low induction of genes involved in the stress response and virulence during starvation (1).…”
Section: Discussionmentioning
confidence: 99%